Analysis of the transformation strain associated with the hexagonal-to-orthorhombic transition in Ti₃Sn - Ivanova, O.I. (Электронная микроскопия и прочность материалов, 2014)
This review is dedicated to the analysis of the hexagonal-to-orthorhombic transition into Ti₃Sn. The place of martensitic transformation into broader category of displacive (diffusionless) transformations is shown from the point of view of a transformation strain associated with the transition. The transformation strain regarded to the transformation into Ti₃Sn was analyzed and the displacive shear-dominant (martensitic) origin of this transition was shown. The latter part of the work is dedicated to the comparison of the volume change and transformation temperature in Ti₃Sn with those into other materials undergoing martensitic transformation. Огляд присвячений аналізу перетворення із гексагональної в орторомбічну фазу в Ti₃Sn. Показано місце мартенситного перетворення в ширшій категорії бездифузійних перетворень з точки зору деформації перетворення. Деформація перетворення в Ti₃Sn проаналізована і зсувний (мартенситний) характер перетворення проілюстровано. Порівняно зміни об’єму та температури перетворення в Ti₃Sn з такими в інших матеріалах, що зазнають мартенситного перетворення. Обзор посвящен анализу превращения из гексагональной в орторомбическую фазу в Ti₃Sn. Показано место мартенситного превращения в более широкой категории бездиффузионных превращений с точки зрения деформации превращения. Деформация превращения в Ti₃Sn проанализирована и сдвиговый (мартенситный) характер превращения показан. Проведено сравнение изменения объема и температуры превращения в Ti₃Sn с этими характеристиками в других материалах, претерпевающих мартенситное превращение.